Financial Distress dan Opini Audit Sesuai Standar Audit (SA) 706 pada Masa Pandemi Covid-19 - Monika, Ni Komang Ita; Mertha, Made (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p16, 2021)
Covid-19 is a global health problem, including Indonesia. Covid-19 has had a huge impaction theicountry's economyias well as the companies affected by it. Many companies experience financial distress and this also has an impact on the audit opinion received by the company. This study aims to examine the effect of financial distress on audit opinion with SA 706. The sample obtained was 534 companies, obtained using purposive sampling technique. The data analysis technique in this research logistic regression analysis. The results of the analysis show that financial distress has an impact on audit opinion with Audit Standards (SA) 706. The theoretical implications of this study can contribute to empirical studies of agency theory and signal theory. The practical implication of this research is that it can be taken into consideration in decision makingbystakeholders and company management. Keywords: Audit Opinion; Audit Standards (SA) 706; Financial Distress; Covid-19.